A palladium-based catalyst for electrochemical dechlorination and preparation method thereof

By mixing the transition metal compound with the organic ligand, metal organic frame powder is prepared, and Pd-based catalysts containing different components and chemical states are formed through spontaneous electrosubstitution reactions, the problem of low catalytic efficiency of Pd-based catalysts in the prior art is solved, and an efficient electrochemical dechlorination reaction is achieved.

CN115323427BActive Publication Date: 2025-03-04ZHEJIANG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210922121.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-02
Publication Date
2025-03-04
Estimated Expiration
2042-08-02

AI Technical Summary

Technical Problem

In the prior art, it is difficult to effectively utilize various chemical components and Pd-based catalysts in chemical states during electrochemical dechlorination, resulting in low catalytic efficiency.

Method used

Metal organic frame powder is prepared by mixing the transition metal compound with the organic ligand, and a Pd-based catalyst containing different components and chemical states is formed by spontaneous electrical replacement reaction. The method is simple to operate and does not require the addition of structural guides, template agents and etchants.

Benefits of technology

High catalytic activity in electrochemical dechlorination reaction is achieved, and the active hydrogen adsorption and dechlorination processes are completed respectively through the synergistic action of multiple components, which significantly improves the dechlorination efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003778005990000011
    Figure HDA0003778005990000011
  • Figure HDA0003778005990000021
    Figure HDA0003778005990000021
  • Figure HDA0003778005990000022
    Figure HDA0003778005990000022
Patent Text Reader

Abstract

The invention discloses a palladium-based catalyst for electrochemical dechlorination and a preparation method thereof. The preparation process of the composite electrocatalyst of the invention is simple to operate, and no structure directing agent, template agent and etching agent need to be added during the reaction. The prepared Pd-based catalyst contains Pd of different components and chemical states at the same time. The obtained Pd-based catalyst is used in a dechlorination reaction to give full play to the synergistic effect of multiple components, and the active hydrogen adsorption and dechlorination processes are completed respectively. The high catalytic activity of the catalyst is confirmed by testing in a dechlorination reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a palladium-based catalyst for electrochemical dechlorination and a preparation method thereof. Background Art

[0002] Chlorinated organic compounds, especially chlorinated aromatic compounds (such as 4-chlorophenol, 4-CP), are widely used, widely polluting and highly toxic organic substances. They will cause serious harm to the human body and the ecology when entering the environment. Therefore, it is of great research significance to find a simple, novel and universal method to prepare catalysts with high dechlorination activity. Since metal Pd has the special function of hydrogen production and lattice hydrogen storage at low overpotential, it has been proved to have excellent performance in electrocatalytic hydrodechlorination (EHDC).

[0003] In the electrocatalytic dechlorination, indirect electrocatalytic hydrogenation dechlorination is the main route, including two key steps: hydrogenation and dechlorination. Among various noble metal electrocatalytic materials, metal Pd not only has the ability to catalyze water molecules (H2O) and hydrogen ions (H + 、H3O + ) has the ability to generate active H* atoms, as well as the ability to adsorb these active H* atoms on its own surface and store them in its own lattice. Its unique properties make it one of the most outstanding catalysts for indirect reductive dechlorination in electrocatalytic dechlorination.

[0004] At present, the research on Pd-based catalysts for dechlorination can be divided into the following aspects: (1) Searching for highly active dechlorination catalysts by regulating the size and morphology of Pd nanomaterials; (2) Optimizing the effect of electrocatalytic dechlorination by doping a second metal with Pd to form a PdM alloy and changing the electronic structure of Pd, such as PdAg, PdAu, PdCu, PdRh, etc. (3) Designing catalysts based on the dechlorination mechanism and efficiently completing the dechlorination process through synergistic effects and division of labor.

[0005] Among them, there are several attempts based on the third catalyst design idea: (1) Through the combination of metal and carrier, such as Pd-anchored Ni(OH)2 / Ni-foam, Pd / NiCo2O4 / NF and Pd / MnO2, the carrier completes the adsorption of H and the Pd component completes the dechlorination step. (2) Bimetallic combination, such as: PdAg, PdAu, etc., by the addition of a second metal, cationized Pd is obtained, and the Pd element completes the hydrogenation and dechlorination steps respectively. (3) Preparation of catalysts containing two different species of Pd 0 and Pd n+The above attempts have proved that the role of each catalyst component in the dechlorination process can be effectively exerted. The realization of synergistic catalysis is a new way for electrochemical dechlorination. In addition, finding a simple, easy and mass-produced method to synthesize Pd-based catalysts with a variety of chemical components and chemical states is a new challenge in the design and synthesis of dechlorination catalysts. Summary of the invention

[0006] In order to solve the defects of the prior art, the purpose of the present invention is to provide a palladium-based catalyst for electrochemical dechlorination and a preparation method thereof. The palladium-based catalyst for electrochemical dechlorination has different chemical states of Pd, and the preparation process is simple to operate. No structure directing agent, template agent and etching agent need to be added during the reaction process, and excellent synergistic effect is shown in the electrochemical dechlorination process.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a palladium-based catalyst for electrochemical dechlorination comprises the following steps:

[0009] (1) mixing a transition metal compound solution and an organic ligand solution uniformly, reacting at 20 to 180° C. for 2 to 8 hours, then cooling the reaction solution to room temperature, centrifuging and washing, and vacuum drying to obtain a metal organic framework powder;

[0010] The transition metal compound is Zn(NO3)2·6H2O, Ni(NO3)2·6H2O or Co(NO3)2·6H2O, preferably Zn(NO3)2·6H2O;

[0011] The organic ligand is dimethylimidazole (2-MeIM);

[0012] The mass ratio of the transition metal compound to the organic ligand is 1:0.5-3.0, preferably 1:0.57-3.0;

[0013] The transition metal compound solution is prepared by dissolving the transition metal compound in methanol or water, with a concentration ranging from 0.004 to 0.105 g / mL, preferably 0.004 to 0.079 g / mL;

[0014] The organic ligand solution is prepared by dissolving the organic ligand in methanol or water, and the concentration range is 0.013-0.088 g / mL;

[0015] The centrifugal washing is to use methanol to centrifuge and wash for multiple times to remove uncoordinated metal ions and 2-methylimidazole; the vacuum drying temperature is 60°C and the time is 8 to 12 hours;

[0016] (2) The metal organic framework powder obtained in step (1) was evenly spread on a porcelain boat and placed in the middle of a tube furnace; first, N2 was continuously passed into the tube furnace (30 min) to remove residual air, and the flow rate was set to 80-100 sccm; before the program started, N2 was replaced with Ar, and the flow rate was changed to 20-50 sccm, and the program process was set to 5°C min in an Ar atmosphere. -1 The temperature is raised to 600-1000°C at a rate of 1.5 °C. After reaching the set temperature, the temperature is kept at this temperature for 2 hours. When the temperature of the tube furnace drops to 300°C after the heat preservation, the atmosphere is changed to N2 until the temperature of the tube furnace drops to room temperature. The solid powder is taken out of the tube furnace for use.

[0017] The N2 is 99.999% high purity N2;

[0018] The Ar is 99.999% high purity Ar;

[0019] (3) dissolving the solid powder obtained in step (2) in a 0.1M HClO4 solution to form a black solution I, and pre-bubbling N2 (20 min) into solution I to remove air from the solution; dissolving PdCl2 in a 0.1M HClO4 solution to form a yellow solution II; adding solution II dropwise to solution I, and continuing to bubble N2 for 3 to 4 h, a spontaneous galvanic replacement reaction occurs in the system, and after the reaction is completed, the solution is centrifuged and washed, and vacuum dried to obtain the palladium-based catalyst;

[0020] The mass ratio of the solid powder to PdCl2 is 8 to 12:1;

[0021] The centrifugal washing is to wash with deionized water for multiple times until the pH of the washing solution is 7; the vacuum drying is to dry in a vacuum oven at 50-60° C. for 6-8 hours.

[0022] The present invention also relates to a palladium-based catalyst obtained by the above preparation method. The obtained Pd-based catalyst containing different components and chemical states can be used as an electrocatalyst in a dechlorination reaction.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention prepares a Pd-based catalyst containing different components and chemical states, the preparation process is simple to operate, and no structure directing agent, template agent and etching agent need to be added during the reaction, and the obtained Pd-based catalyst is used in a dechlorination reaction. The preparation process of the composite electrocatalyst of the present invention is simple to operate, and Pd containing different components and chemical states can give full play to the synergistic effect of multiple components to complete active hydrogen adsorption and dechlorination processes respectively. The high catalytic activity of the catalyst is confirmed by testing in a dechlorination reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1These are SEM images of different transition metal compound precursor MOFs in Examples 1 to 4; (A) ZIF-67, (B) Ni-ZIF, (C) ZIF-8-P, (D) ZIF-8-NS.

[0026] Figure 2 TEM images of Pd-based catalysts derived from different transition metal compound MOFs in Examples 1 to 7; (A) PdCo / CN-700, (B) PdNi / CN-700, (C) PdZn / CN-P-700, (D) PdZn / CN-NS-700, (E) PdZn / CN-NS-600, (F) PdZn / CN-NS-800, (G) PdZn / CN-NS-1000.

[0027] Figure 3 This is the XPS graph of the Pd element in the catalysts in Examples 5 to 7.

[0028] Figure 4 The performance diagrams of the dechlorination performance tests of the Pd-based catalysts in Examples 1 to 7; (A) PdCo / CN-700, PdNi / CN-700, PdZn / CN-P-700 and PdZn / CN-NS-700; (B) PdZn / CN-NS-600, PdZn / CN-NS-800 and PdZn / CN-NS-1000.

[0029] Figure 5 These are performance diagrams of the dechlorination stability test of the Pd-based catalysts in Examples 6 to 7; (A) PdZn / CN-NS-800, (B) PdZn / CN-NS-1000. DETAILED DESCRIPTION

[0030] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0031] Example 1

[0032] Synthesis of the precursor ZIF-67: Weigh 5.80g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and dissolve it in 75mL of methanol, then weigh 6.57g of dimethylimidazole (2-MeIM) and dissolve it in an equal volume of methanol. Stir them for 15min respectively, then mix the two solutions and stir them continuously for 4h at room temperature to obtain a purple turbid solution. Wash the obtained purple precipitate with methanol by centrifugation for more than 4 times to remove uncoordinated cobalt ions and 2-methylimidazole, and dry it in vacuum at 60°C overnight. The obtained purple powder is the target metal organic framework ZIF-67.

[0033] Synthesis of carrier Co / CN-700: Spread the synthesized ZIF-67 precursor powder evenly on a porcelain boat and place it in the middle of a tube furnace. First, pass high-purity N2 into the tube furnace for 30 minutes to remove residual air, with a flow rate of 100 sccm. Before the program starts, replace high-purity N2 with high-purity Ar, with a flow rate of 20 sccm, and set the program process to 5°C min in an Ar atmosphere. -1 The temperature was raised to 700℃ at a rate of 1.5℃. After reaching 700℃, the temperature was kept for 2h. ZIF-67 was carbonized and reduced to black powder Co / CN in the tube furnace. When the temperature of the tube furnace dropped to about 300℃ after the reaction, the atmosphere was changed to N2 until the temperature of the tube furnace dropped to room temperature. The sample was taken out of the tube furnace and defined as Co / CN-700.

[0034] The SEM image of ZIF-67 (CoMOF) was obtained, as shown in Figure 1A.

[0035] Depend on Figure 1 As can be seen from Figure A, the obtained ZIF-67 presents a regular dodecahedral morphology, the particle surface is smooth, and the distribution is relatively uniform.

[0036] Synthesis of PdCo / CN-700: Weigh 50 mg of ground Co / CN-700 and dissolve it in 50 mL of 0.1 M HClO4 solution to form a black solution I. Pre-pass N2 into solution I for 20 min to remove air from the solution. Weigh 6.83 mg of PdCl2 and dissolve it in 10 mL of 0.1 M HClO4 solution to form a yellow solution II. Stir for 15 min until PdCl2 is completely dissolved into a yellow clear solution. Use a dropper to slowly drop solution II into solution I. Continue to pass N2 bubbling for 4 h to allow spontaneous electrical replacement reaction to occur. Wash with deionized centrifuge for more than four times until the pH of the washing solution is 7. Vacuum dry at 60 ° C overnight to obtain PdCo / CN-700 catalyst. The PdCo catalyst is obtained as shown in A in 2. By Figure 2 As can be seen from Figure A, the average size of the obtained PdCo / CN-700 metal nanoparticles is about 10 to 20 nm, and they are dispersed relatively evenly.

[0037] The dechlorination performance of the catalyst PdCo / CN-700 was tested by constant current electrolysis. The constant current electrolysis experiment was carried out in a Shanghai Chenhua CHI-660D electrochemical workstation. A two-chamber H-type electrolyzer was used in the experiment. The cathode and anode were separated by a Nafion-117 cation exchange membrane. During electrolysis, the cathode was a carbon paper electrode (2×2 cm) modified with 5 mg of Pd-based catalyst. 2 ), the anode is a graphite rod (2×2cm 2), the reference electrode is an Ag / AgCl electrode equipped with a saturated KCl solution, and the entire reaction process is controlled at a constant temperature of 30°C using an SDC-6 low-temperature constant temperature circulator. The cathode of the electrolytic cell is equipped with 30mL 100mM pH=7 phosphate buffer (containing 1mM substrate 4-CP), and the anode is equipped with 30mL 100mM pH=7 phosphate buffer. The cathode solution is stirred throughout the electrolysis process, and high-purity N2 is passed through the cathode solution for 20min before electrolysis, with a flow rate of 40sccm. At the beginning of the electrolysis process, the N2 flow rate is adjusted to 20sccm. In this experiment, all constant current electrolysis durations are set to 10800s, and about 0.5mL of solution is taken from the cathode electrolyte at intervals for further analysis. The concentrations of the substrate (4-chlorophenol, 4-CP) and product (phenol, PhOH) after the electrolysis experiment are quantitatively analyzed using high-performance liquid chromatography (model: Thermo Fisher 3000). The configuration of Thermo Fisher Scientific 3000 HPLC includes chromatographic column, photodiode detector, etc. 甲醇 :V 水 =4:1 mixed solution (containing 30mL H3PO4) was used as the mobile phase, the injection volume was 20μL, and the flow rate was 1mL·min -1 The injection temperature and column temperature were both 25°C, and the detection wavelength was 280nm. The standard curve was measured by external standard method, and the sample solution at each time point in the electrolysis process was quantitatively analyzed.

[0038] Test results such as Figure 4 As shown in A.

[0039] Example 2

[0040] Synthesis of Ni-ZIF precursor: 1.57 g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) was weighed and dissolved in 15 mL of methanol, and then 0.89 g of dimethylimidazole (2-MeIM) was weighed and dissolved in an equal volume of methanol. After stirring for 15 min, the two solutions were mixed and stirred at room temperature for 2 h to obtain a green mixed solution. The mixed solution was poured into a microwave tube and placed in a microwave synthesizer at 10 °C·min -1 The temperature was raised to 180°C at a rate of 1.04 °C and the reaction was continued at 180°C for 2 h. After the reaction, the temperature in the reaction tube dropped to room temperature. The obtained dark red-brown turbid liquid was centrifuged and washed 4 times or more with methanol to remove uncoordinated nickel ions and 2-methylimidazole. The solution was dried in vacuum at 60°C overnight to obtain a dark brown powder, which was the target metal-organic framework Ni-ZIF.

[0041] Synthesis of carrier Ni / CN-700: Spread the synthesized Ni-ZIF precursor powder evenly on a porcelain boat and place it in the middle of a tube furnace. First, pass high-purity N2 into the tube furnace for 30 minutes to remove residual air, with a flow rate of 100 sccm. Before the program starts, replace high-purity N2 with high-purity Ar, with a flow rate of 20 sccm, and set the program process to 5°C min in an Ar atmosphere. -1 The temperature was raised to 700℃ at a rate of 1.5℃. After reaching 700℃, the temperature was kept for 2h. Ni-ZIF was carbonized and reduced to black powder Ni / CN in the tube furnace. When the temperature of the tube furnace dropped to about 300℃ after the reaction, the atmosphere was changed to N2 until the temperature of the tube furnace dropped to room temperature. The sample was taken out of the tube furnace and defined as Ni / CN-700.

[0042] The SEM image of NiMOF is shown in Figure 1B. Figure 1 In B, it can be seen that the obtained Ni-ZIF is a flower-like particle composed of a two-dimensional layer structure with a smooth layer surface and a particle size of about 5 to 7 μm.

[0043] The synthesis method of PdNi / CN-700 is also through spontaneous galvanic replacement. The experimental scheme is the same as that of PdCo / CN-700, except that the carrier Co / CN-700 is replaced by Ni / CN-700. The TEM image of the PdNi catalyst is shown in Figure 2B. Figure 2 From B, it can be seen that the size of the metal nanoparticles in the obtained PdNi / CN-700 bimetallic catalyst is basically between 10 and 20 nm.

[0044] The dechlorination performance test method of catalyst PdNi / CN-700 is the same as that in Example 1. The test results are as follows: Figure 4 As shown in A.

[0045] Example 3

[0046] Synthesis of the precursor ZIF-8-P: Weigh 11.90g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and dissolve it in 150mL of methanol, then weigh 13.14g of dimethylimidazole (2-MeIM) and dissolve it in an equal volume of methanol. After stirring for 15min, the two solutions were mixed and stirred continuously for 4h at room temperature to obtain a white turbid solution. The obtained white precipitate was washed with deionized water by centrifugation for more than 4 times to remove uncoordinated zinc ions and 2-methylimidazole, and vacuum dried at 60°C overnight to obtain a white powder, which is dodecahedral ZIF-8-P.

[0047] Synthesis of carrier Zn / CN-P-700: Spread the synthesized ZIF-8-P precursor powder evenly on a porcelain boat and place it in the middle of a tube furnace. First, pass high-purity N2 into the tube furnace for 30 minutes to remove residual air, with a flow rate of 100 sccm. Before the program starts, replace high-purity N2 with high-purity Ar, with a flow rate of 20 sccm, and set the program process to 5°C min in an Ar atmosphere. -1 The temperature was raised to 700℃ at a rate of 1.5℃. After reaching 700℃, the temperature was kept for 2h. ZIF-8-P was carbonized and reduced to black powder Zn / CN-P in the tube furnace. When the temperature of the tube furnace dropped to about 300℃ after the reaction, the atmosphere was changed to N2 until the temperature of the tube furnace dropped to room temperature. The sample was taken out of the tube furnace and defined as Zn / CN-P-700.

[0048] The SEM image of the obtained ZIF-8-P is shown in Figure 1C. Figure 1 From Figure C, we can see that the obtained ZIF-8-P is a dodecahedral particle with a particle size of about 0.5 μm.

[0049] The synthesis method of PdZn / CN-P-700 is also through spontaneous electrochemical replacement. The experimental scheme is the same as that of PdCo / CN-700, except that the carrier Co / CN-700 is replaced by Zn / CN-P-700. The TEM image of the PdZn catalyst is shown in Figure 2C. Figure 2 It can be seen from Figure C that no obvious metal agglomerate particles were observed on the surface of the obtained PdZn / CN-P-700, indicating that the Pd-based catalyst is relatively dispersed as a whole, and abundant and uniform pores can be seen.

[0050] The dechlorination performance test method of catalyst PdZn / CN-P-700 is the same as that in Example 1. The test results are as follows: Figure 4 As shown in A.

[0051] Example 4

[0052] Synthesis of the precursor ZIF-8-NS: Weigh 0.66g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and dissolve it in 150mL of deionized water, then weigh 1.97g of dimethylimidazole (2-MeIM) and dissolve it in an equal volume of deionized water. Stir them for 15min respectively, then mix the two solutions and stir them continuously for 8h at room temperature to obtain a white turbid solution. The obtained white precipitate was washed with deionized water by centrifugation for more than 4 times to remove uncoordinated zinc ions and 2-methylimidazole, and then dried in vacuum at 60°C overnight to obtain a white powder, which is the nanosheet ZIF-8-NS.

[0053] Synthesis of carrier Zn / CN-NS-700: Spread the synthesized ZIF-8-NS precursor powder evenly on a porcelain boat and place it in the middle of a tube furnace. First, pass high-purity N2 into the tube furnace for 30 minutes to remove residual air, with a flow rate of 100 sccm. Before the program starts, replace high-purity N2 with high-purity Ar, with a flow rate of 20 sccm, and set the program process to 5°C min in an Ar atmosphere. -1 The temperature was raised to 700℃ at a rate of 1.5℃. After reaching 700℃, the temperature was kept for 2h. ZIF-8-NS was carbonized and reduced to black powder Zn / CN-NS in the tube furnace. When the temperature of the tube furnace dropped to about 300℃ after the reaction, the atmosphere was changed to N2 until the temperature of the tube furnace dropped to room temperature. The sample was taken out of the tube furnace and defined as Zn / CN-NS-700.

[0054] The SEM image of the obtained ZIF-8-NS is shown in Figure 1D. Figure 1 As can be seen from Figure D, the obtained ZIF-8-NS is a thin sheet nanosheet with a particle size of about 3 to 5 μm.

[0055] The synthesis method of PdZn / CN-NS-700 is also through spontaneous electroreplacement, and the experimental scheme is the same as that of PdCo / CN-700, except that the carrier Co / CN-700 is replaced by Zn / CN-NS-700. The TEM image of the PdZn catalyst is shown in Figure 2D. Figure 2 No obvious metal agglomerate particles are observed in Figure D, indicating that the metal component particles in the obtained PdZn / CN-NS-700 are small and relatively dispersed as a whole. In addition, abundant and uniform pores can be observed in the figure.

[0056] The dechlorination performance test method of catalyst PdZn / CN-NS-700 is the same as that in Example 1. The test results are as follows: Figure 4 As shown in A.

[0057] Example 5

[0058] Synthesis of carrier Zn / CN-NS-600: The ZIF-8-NS precursor powder synthesized in Example 4 was evenly spread on a porcelain boat and placed in the middle of a tube furnace. First, high-purity N2 was continuously passed through the tube furnace for 30 minutes to remove residual air, and the flow rate was set to 100 sccm. Before the program started, high-purity N2 was replaced with high-purity Ar, and the flow rate was changed to 20 sccm. The program process was set to 5°C·min in an Ar atmosphere. -1The temperature was raised to 600℃ at a rate of 1.5℃. After reaching 600℃, the temperature was kept for 2h. ZIF-8-NS was carbonized and reduced to black powder Zn / CN-NS in the tube furnace. When the temperature of the tube furnace dropped to about 300℃ after the reaction, the atmosphere was changed to N2 until the temperature of the tube furnace dropped to room temperature. The sample was taken out of the tube furnace and defined as Zn / CN-NS-600.

[0059] The synthesis of PdZn / CN-NS-600 was also carried out by spontaneous electrochemical replacement. The experimental scheme was the same as that of PdCo / CN-700, except that the carrier Co / CN-700 was replaced by Zn / CN-NS-600. The TEM image of the PdZn / CN-NS-600 catalyst was obtained, as shown in Figure 2E. Figure 2 It can be seen from Figure E that there is no obvious agglomeration of metal particles in the sample, indicating that the metal component particles in the obtained PdZn / CN-NS-600 are small and evenly distributed.

[0060] The chemical state of the Pd element in the catalyst PdZn / CN-NS-600 is as follows: Figure 3 The dechlorination performance test method of the catalyst is the same as that in Example 1, and the test results are shown in Figure 4 As shown in B.

[0061] Example 6

[0062] Synthesis of carrier Zn / CN-NS-800: The ZIF-8-NS precursor powder synthesized in Example 4 was evenly spread on a porcelain boat and placed in the middle of a tube furnace. First, high-purity N2 was continuously passed through the tube furnace for 30 minutes to remove residual air, and the flow rate was set to 100 sccm. Before the program started, high-purity N2 was replaced with high-purity Ar, and the flow rate was changed to 20 sccm. The program process was set to 5°C·min in an Ar atmosphere. -1 The temperature was raised to 800℃ at a rate of 1.5℃. After reaching 800℃, the temperature was kept for 2h. ZIF-8-NS was carbonized and reduced to black powder Zn / CN-NS in the tube furnace. When the temperature of the tube furnace dropped to about 300℃ after the reaction, the atmosphere was changed to N2 until the temperature of the tube furnace dropped to room temperature. The sample was taken out of the tube furnace and defined as Zn / CN-NS-800.

[0063] The synthesis method of PdZn / CN-NS-800 is also through spontaneous electrochemical replacement. The experimental scheme is the same as that of PdCo / CN-700, except that the carrier Co / CN-700 is replaced by Zn / CN-NS-800. The TEM image of the PdZn / CN-NS-800 catalyst is shown in Figure 2F. Figure 2 It can be seen from Figure F that there is no obvious agglomeration of metal particles in the sample, indicating that the metal component particles in the obtained PdZn / CN-NS-800 are small and evenly distributed.

[0064] The chemical state of the Pd element in the catalyst PdZn / CN-NS-800 is as follows: Figure 3 As shown, in this sample, Pd 3d 5 / 2 Three peaks were fitted at binding energies of 335.7 eV, 337.8 eV, and 338.8 eV, which were respectively attributed to Pd 0 and cationized Pd n+ The ionization state is related to the coordination elements N and Cl. The catalyst dechlorination performance test method is the same as in Example 1, and the test results are as follows: Figure 4 As shown in B, the stability evaluation method of the catalyst dechlorination is to evaluate the catalyst stability by washing the carbon paper electrode containing the Pd-based catalyst after each electrolysis. Figure 5 As shown in A.

[0065] Example 7

[0066] Synthesis of carrier Zn / CN-NS-1000: The ZIF-8-NS precursor powder synthesized in Example 4 was evenly spread on a porcelain boat and placed in the middle of a tube furnace. First, high-purity N2 was continuously passed through the tube furnace for 30 minutes to remove residual air, and the flow rate was set to 100 sccm. Before the program started, high-purity N2 was replaced with high-purity Ar, and the flow rate was changed to 20 sccm. The program process was set to 5°C·min in an Ar atmosphere. -1 The temperature was raised to 1000℃ at a rate of 1000℃ and kept at 1000℃ for 2h. ZIF-8-NS was carbonized and reduced to black powder Zn / CN-NS in the tube furnace. When the temperature of the tube furnace dropped to about 300℃ after the reaction, the atmosphere was changed to N2 until the temperature of the tube furnace dropped to room temperature. The sample was taken out of the tube furnace and defined as Zn / CN-NS-1000.

[0067] The synthesis method of PdZn / CN-NS-1000 is also through spontaneous electrochemical replacement. The experimental scheme is the same as that of PdCo / CN-700, except that the carrier Co / CN-700 is replaced by Zn / CN-NS-1000. The TEM image of the PdZn / CN-NS-1000 catalyst is shown in Figure 2G. Figure 2 It can be seen from Figure G that there is no obvious agglomeration of metal particles in the sample, indicating that the metal component particles in the obtained PdZn / CN-NS-1000 are small and evenly distributed.

[0068] The chemical state of the Pd element in the catalyst PdZn / CN-NS-1000 is as follows: Figure 3 The dechlorination performance test method of the catalyst is the same as that in Example 1, and the test results are shown in Figure 4 As shown in B, the stability test of the catalyst dechlorination is as follows Figure 5 As shown in B.

Claims

1. A method for preparing a palladium-based catalyst, characterized in that: The steps include: (1) mixing a transition metal compound solution and an organic ligand solution uniformly, reacting at 20 to 180° C. for 2 to 8 hours, then cooling the reaction solution to room temperature, centrifuging and washing, and vacuum drying to obtain a metal organic framework powder; The transition metal compound is Zn(NO3)2·6H2O, Ni(NO3)2·6H2O or Co(NO3)2·6H2O; The organic ligand is 2-methylimidazole; (2) The metal organic framework powder obtained in step (1) was evenly spread on a porcelain boat and placed in the middle of a tube furnace; first, N2 was continuously introduced into the tube furnace to remove residual air, and the flow rate was set to 80-100 sccm; before the program started, N2 was replaced with Ar, and the flow rate was changed to 20-50 sccm, and the program process was set to 5°C min in an Ar atmosphere. -1 The temperature is raised to 600-1000°C at a rate of 1.5 °C. After reaching the set temperature, the temperature is kept at this temperature for 2 hours. When the temperature of the tube furnace drops to 300°C after the heat preservation, the atmosphere is changed to N2 until the temperature of the tube furnace drops to room temperature. The solid powder is taken out of the tube furnace for use. (3) The solid powder obtained in step (2) is dissolved in a 0.1M HClO4 solution to form a black solution I, and N2 is pre-bubbled into solution I to remove air from the solution; PdCl2 is dissolved in a 0.1M HClO4 solution to form a yellow solution II; Solution II is added dropwise to Solution I, and N2 bubbling is continued for 3 to 4 hours, so that a spontaneous galvanic replacement reaction occurs in the system. After the reaction is completed, the solution is washed by centrifugation and dried in a vacuum to obtain the palladium-based catalyst.

2. The preparation method of a palladium-based catalyst as claimed in claim 1, wherein In step (1), the mass ratio of the transition metal compound to the organic ligand is 1:0.5-3.

0.

3. The preparation method of palladium-based catalyst as claimed in claim 1, characterized in that, In step (1), the transition metal compound solution is prepared by dissolving the transition metal compound in methanol or water, and the concentration range is 0.004 to 0.105 g / mL.

4. The preparation method of a palladium-based catalyst as claimed in claim 1, wherein In step (1), the organic ligand solution is prepared by dissolving the organic ligand in methanol or water, and the concentration range is 0.013 to 0.088 g / mL.

5. The preparation method of palladium-based catalyst as claimed in claim 1, characterized in that, In step (3), the mass ratio of the solid powder to PdCl2 is 8 to 12:

1.

6. A palladium-based catalyst obtained by the preparation method according to any one of claims 1 to 5.

7. Use of the palladium-based catalyst as claimed in claim 6 in an electrochemical dechlorination reaction.

Citation Information

Patent Citations

  • Preparation method of supported palladium catalyst

    CN106423251A